2006
DOI: 10.1002/rra.933
|View full text |Cite
|
Sign up to set email alerts
|

Flow variability and macroinvertebrate community response within riverine systems

Abstract: • This is the pre-peer reviewed version of the article, which has been published in final form at: http://dx.doi.org/10.1002/rra.933

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
196
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(204 citation statements)
references
References 50 publications
5
196
1
Order By: Relevance
“…In both applications, the magnitude of the hydrological regime was quantified by four indices: mean, maximum, minimum and standard deviation of the annual (single year) or long-term (1980 -1999) discharge time-series. Prior to classification of the flow regime, discharges (m 3 s -1 ) were converted to runoff (mm month -1 ) and transformed to zscores (mean = 0; standard deviation = 1) to remove any statistical bias associated with catchment area (Monk et al, 2006). The hydrological time-series for each site was divided into hydrological years commencing in August, since July was identified as the most frequent month of minimum runoff across the selected rivers.…”
Section: Data Analysesmentioning
confidence: 99%
See 4 more Smart Citations
“…In both applications, the magnitude of the hydrological regime was quantified by four indices: mean, maximum, minimum and standard deviation of the annual (single year) or long-term (1980 -1999) discharge time-series. Prior to classification of the flow regime, discharges (m 3 s -1 ) were converted to runoff (mm month -1 ) and transformed to zscores (mean = 0; standard deviation = 1) to remove any statistical bias associated with catchment area (Monk et al, 2006). The hydrological time-series for each site was divided into hydrological years commencing in August, since July was identified as the most frequent month of minimum runoff across the selected rivers.…”
Section: Data Analysesmentioning
confidence: 99%
“…Previous research has demonstrated the utility of the LIFE methodology compared to other metrics (e.g., total abundance, number of taxa and diversity indices) when using data recorded in log 10 abundance categories at the family level; and that the LIFE score is a more appropriate and statistically powerful metric compared to other macroinvertebrate biotic indices (e.g., BMWP and ASPT) when examining the ecological response to flow regime variability (Monk et al, 2006). Other research has shown the LIFE score to be sensitive to both natural river flow variability and anthropogenic modification (Extence et al, 1999;Dunbar and Clarke, 2004).…”
Section: Data Analysesmentioning
confidence: 99%
See 3 more Smart Citations